2012
DOI: 10.1007/s12272-012-0505-0
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer activity of undecapeptide analogues derived from antimicrobial peptide, Brevinin-1EMa

Abstract: In spite of great advances in cancer therapy, cancer remains the major cause of death throughout the world. The increasing resistance of cancer cells towards current anticancer drugs requires development of anticancer agents with a new mode of action. Some antimicrobial peptides have become therapeutic candidates as new anticancer agents. As part of an effort to develop new antimicrobial and/or anticancer agents from natural peptides with low molecular weights, we have investigated the shortest bioactive analo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Additionally, anti-cancer properties of Brevinin-1EMa derivatives were investigated against seven tumor cell lines, such as A498 (kidney), A549 (lung), HCT116 (colon), MKN45 (stomach), PC-3 (prostate), SK-MEL-2 (skin), and SK-OV-3 (ovary). (Kang et al 2012). There was a report concerning the anti-cancer function of modified Brevinin, like dicarba-Brevinin-1BYa.…”
Section: Anti-cancer Effects Of Brevininmentioning
confidence: 99%
“…Additionally, anti-cancer properties of Brevinin-1EMa derivatives were investigated against seven tumor cell lines, such as A498 (kidney), A549 (lung), HCT116 (colon), MKN45 (stomach), PC-3 (prostate), SK-MEL-2 (skin), and SK-OV-3 (ovary). (Kang et al 2012). There was a report concerning the anti-cancer function of modified Brevinin, like dicarba-Brevinin-1BYa.…”
Section: Anti-cancer Effects Of Brevininmentioning
confidence: 99%
“…In this investigated the anticancer activity of four undecapeptides against seven tumor cell lines such as A498 (kidney), A549 (lung), HCT116 (colon), MKN45 (stomach), PC-3 (prostate), SK-MEL-2 (skin) and SK-OV-3 (ovary). Result showed that the GA-K4 (FLKWLFKWAKK-NH2), which had the most potent antimicrobial activity of the four undecapeptides, also exhibited the most potent anticancer activity snf synergistic effect in combination with doxorubicin [20].…”
Section: Kang Et Al (2012)mentioning
confidence: 99%
“…Then some researches revealed some common structural features of Brevinin-1 family, Proline is often the 14th residue in the sequence [ 10 ], and most of them have a cyclic heptapeptide (Cys 18 -(Xaa)4-Lys-Cys 24 ) called Rana-box at the C-terminal, which forms a disulfide bridge [ 11 ]. Brevinin-1 peptides usually demonstrate a broad-spectrum antimicrobial activity against Gram-positive and Gram-negative bacteria and strains of pathogenic fungi [ 9 ], and some analogues can inhibit the growth of cancer cell lines [ 12 ]. Peptides in the Brevinin-1 family are linear, amphipathic and cationic.…”
Section: Introductionmentioning
confidence: 99%